A Case of Myeloproliferative Neoplasm with BCR-FGFR1 Rearrangement: Favorable Outcome after Haploidentical Allogeneic Transplantation - Villafuerte-Gutiérrez, Paola; López Rubio, Montserrat; Herrera, Pilar; Arranz, Eva (Case Reports in Hematology, 2018)
Hematopoietic myeloproliferative neoplasms with FGFR1 rearrangement result in the 8p11 myeloproliferative syndrome that in the current Word Health Organization classification is designated as “myeloid and lymphoid neoplasm with FGFR1 abnormalities.” We report the case of a 66-year-old man who had clinical features that resembled chronic myeloid leukaemia (CML), but bone marrow cytogenetic and fluorescent in situ hybridization (FISH) studies showed t(8;22)(p11;q11) and BCR-FGFR1 fusion gene. He was initially managed with hydroxyurea, and given the aggressive nature of this disease, four months later, the patient underwent an allogeneic hematopoietic stem-cell transplantation (HSCT) from an HLA-haploidentical relative. Currently, HSCT may be the only therapeutic option for long-term survival at least until more efficacious tyrosine kinase inhibitors (TKIs) become available.